Next generation sequencing and bio-informatics analysis for the investigation of the vaginal bacterial microflora of clinically healthy mares - Mataragka, Antonia; Symeonidou, Andrianna; Ikonomopoulos, John; Tzimotoudis, Nikolaos; Diakoudi, Georgia; Lanave, Gianvito; Decaro, Nicola; Papakonstantinou, Eleni; Vlachakis, Dimitrios (Acta Scientiarum. Animal Sciences, 2025)
This study was focused on the investigation of the constitution of the vaginal bacterial microflora of mares, using 16Sr-RNA next generation sequencing and bio-informatics analysis. Samples were collected from the inner vaginal wall of 30 clinically healthy adult mares from various locations in central Greece. Successful reads were retrieved from 28 samples resulting to the presumptive identification of 192 bacterial species belonging to 87 genera. None of the bacterial genera or species that were detected was present in all the test samples, which indicates that the vaginal bacterial microflora of the study population is diverse. The bacterial genera detected the most in the test samples were Staphylococcus (89%) and Acinetobacter (54%). The bio-informatics analysis produced evidence of a much richer microbiota for the Greek native, compared to the Arabian and other breeds, and indicated variations in its constitution associated with the reproduction and vaccination records.